النخبة الوطنية السياسية المغربية والحرب الأهلية الاسبانية 1936-1939 - كنيوة, هيبة (University of Eloued جامعة الوادي, 2022)
عانت اسبانيا من حرب أهلية على امتداد الفترة 1936-1939 عصفت بالحكم الجمهوري وتمكن فرانسيسكوا فرنكوا من السيطرة على الحكم في 30 مارس 1939 وخلال هذه الفترة كانت مواقف النخب المغاربية بالجهة الشمالية متأرجحة بين الحياد في البداية وحتى رفض تجنيد المغاربة فيها والانحياز فيما بعد لحكم فرنكوا خاصة انه اتخذ الجهة الشمالية منطلقا لعمالياته العسكرية والسياسية وتطبيقه لسياسة العنف تارة وسياسة الاحتواء تارة أخرى اتجاهها واختلفت النخب الجنوبية في موقفها نوعا ما عن نظيرتها الشمالية، وفي إطار سياسة الاحتواء تأسست الأحزاب السياسية بالجهة الشمالية، مما أثر على المسار الوحدوي للحركة الوطنية المغربية بالانشقاق على امتداد الفترة. Spain experienced a civil war between 1936 and 1939, which led to the fall of the republican government. On March 30, 1939, Francisco Franco succeeded in controlling the government. During this period, the positions of the North African elites in the north swung between neutrality at the beginning and even the refusal to recruit Moroccans in this war. And the bias of Franco's government. Especially the northern side which took the starting point of their military and political operations and the application of the policy of violence and sometimes a policy of containment. The Southern elites differ somewhat in their positions from their Northern counterparts, under the policy of containment of the political parties that have been established in the North. This affected the unified path of the Moroccan national movement in this period.
مقال